Assessment of oral health hygiene among high school girls of Bengaluru city, India - Shireen, Nimra; T. S., Ranganath (International Journal Of Community Medicine And Public Health, 2017)
Background: Oral health is an essential component of general health and quality of life. Dental caries is a major oral public health problem particularly among the children and adolescents. The schools remain an important setting, offering an efficient and effective way to reach children worldwide. Hence, our study aims to assess the oral health hygiene and prevalence of dental caries among high school girls of Bengaluru city - south zone. Methods: A cross sectional study was conducted for a period of four months (i.e.) September 2015 to December 2015 among high school girls of Bengaluru city. They were examined for their oral care, presence of caries and data regarding oral health hygiene was collected by using a semi-structured, indigenous, interviewer based questionnaire. Results: The mean age was 14.2+0.57 years. Majority of the girls (74.4%) said that they brush once daily; 36.8% were unaware about the type of tooth brush used by them. Only few students (14.8%) were using fluoride toothpaste; 72% girls brush their teeth in horizontal direction; 23.2% clean their tongue and 20% use mouth wash; 44% rinse their mouth after eating a meal. Nearly half of the study sample (45.2%) were suffering from dental caries, with mean DMFT score 2.54. Conclusions: Oral health hygiene habits among the study population were poor and needs to be improved. Awareness among the students about maintaining good oral health can be generated by involving the school teachers as they are considered as role models by the students.